Uso de 5 sustratos y 4 dósis de hormonagro en multiplicación de rosas tropicales - Illescas Heras, Ramón Andrés (2006)
At the Greenhouse of the Agropecuary Sciences Faculty, during the winter season-2006, it was carried out a research in order to determi-nate five substrates for the rooting of tropical rose stakes, treated with four dilutions of the hormone Naphtalenacetic acid, traded as Hor-monagro # 1 by the enterprise Ecuaquimica. The planned objectives were: 1. To test 5 types of substrates for the rooting of tropical rose stakes. 2. To determine the doses of Hormonagro #1 which produced the higher amounts of roots in the rose stakes. 3. To evaluate the growing of tips during the 120 days of treatment, from the application of the hormone until the planting in the substrates. The research was started with the collection of rose stakes from parent material with good phyto-sanitary state. In advance, at the greenhouse there were prepared the substrates for rooting, which consisted in : sand screened with 0,2 mm mesh; Peat, Zeolite, agricultural soil+sand+humus, and Agricultural soil+organic matter+Zeolite. All the substrates were codi-fied as A1, A2, A4 and A5, respectively. The hormone used for the growing stimulation of roots was Hormonagro #1 or Naphtalenacetic Acid, with four dilutions and time of inmersion of the stakes codified as B1, B2, B3 and B4. 20 treatments were obtained from the combina-tion of the above mentioned factors, which were assigned to experi-mental units formed by three stakes, following the principles of com-pletely randomized design with three reapplications. The statistical analysis showed high significance for the substrates in the evaluation of number of tips per stake, number of primary and secondary roots and length of roots. The concentrations of Hormonagro # 1 influenced in the number of roots and their lengths. From the substrates tested, the best results were obtained with the Peat and Sand substrate.